Strukturirovanie amplitudno-prostranstvennych charakteristik cikla plavanija junych krolistov - Olkhovskaya, O. G.; Ponimasov, O. E.; Antonov, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article discusses the organization of the training process aimed at the coordinated development of physical qualities and the formation of the technique of swimming chosen for specialization. The dynamics of the amplitude-spatial indicators of free style girls and boys in the process of the initial sports specialization is studied. The metric parameters of swimming are determined, which determine the effectiveness of the synchronized formation of technical and physical fitness. The principle of differentiation of the applied training tools, specific methods of training synchronizing training of young swimmers at the stage of basic training is disclosed. The research results characterizing the effectiveness of the synchronized formation of technical and physical fitness of young swimmers are presented.